Effects of Raphani Semen on Immuno-response in the Mouse Model of allergi Asthma - Jai-Young, Park; Ki-Chul, Park; Hee-Soo, Park (Korean Pharmacopuncture Institute, 2002)
Objective: This study was eanied out to investigate the effects of Raphani Semen on immuno-response in the mouse model of allergic asthma. Methods: In this study, BALB/C mice were divided into 6 groups: Normal (Non-treated group), Control (Group with not treated after allergic sensitization and induction by ovalbumin), Treat I (Group with the oral administration of saline after allergic sensitization and induction by ovalbumin), Treat n (Allergic asthma group treated with acupuncture (BL 13)), Treat III (Allergic asthma group treated with the oral administration of Raphani Semen) and Treat lV (Allergic asthma group treated with the herbal-acupuncture of Raphani Semen (BL 13)). The effect on cytokine was assessed by measuring cytokine (lL-2, IL-4, IL-5, IL-10, IL-12, IFN-r) in bronchoalveoar lavage fluid(ELISA). ResuJts : The results obtained as follows: 1. The production of Interleukin-2 was decreased significantly in Treat I group, Treat n group and Treat IV group as compared with Control group. 2. The production of Interleukin-4 was decreased significantly in Treat I group, Treat II group and Treat IV group as compared with Control group. Among them. the production of Interleukin-4 was decreased remarkably in Treat IV group as compared with other groups. 3. The production of Interleukin-5 was decreased significantly in Treat I group and Treat IV group as compared with Control group. 4. The production of Interleukin-10 was decreased significantly in Treat I group and Treat III group as compared with Control group. 5. The production of Interleukin-12 was all decreased significantly in Treat I group, Treat n group, Treat m group and Treat IV group as compared with Control group. 6. The production of Intelferon- showed no significant changes in Treat I group, Treat n group. Treat m group and Treat Ⅳ group as compared with Control group. Conclusion: These results show that the production of Interleukin-4, 5 was decreased significantly in aJlergic asthma group treated with the herbal-acupuncture of Raph Semen (BL 13), It is known that inactivity of Th2 cell constrained the revelation and controlled hypersenstive action. As to this mechanism, it is suggested that the herbal-acupuncture of Raphani Semen(BL 13) constrained the revelation of allergic asthma.